أثر ستراتيجية (lee) في تنمية الفهم القرائي عند تلاميذ الصّف الخامس الابتدائي (Journal of the College of Basic Education, 2025)
The current research aims to identify the impact of the (lee) strategy on developing reading comprehension among the fifth grade primary students. Reading according to the lee strategy and between the mean scores of the students of the control group studying reading material according to the usual method in the reading comprehension test.The researcher followed the experimental method, and an experimental design with partial control. As for the research community, it was determined by the fifth grade primary students in the General Directorate of Education of Baghdad / Al-Rusafa II, and the researcher randomly selected the “Green Valley” elementary school as a sample for his research. student, and the researcher was statistically equivalent between the two research groups using the variables: the chronological age calculated in months, the parents’ education, and the Arabic language achievement scores in the previous academic year.The researcher prepared a reading comprehension test consisting of 30 objective test items, and the psychometric characteristics of the test were verified before applying it. Using the t-test for two independent samples, the researcher concluded that there were statistical differences at the level of significance (0.05) for the benefit of the experimental group students. The researcher recommended the adoption of the lee strategy in teaching the content of the reading material for the fifth grade of primary school, and suggests building similar studies in the intermediate and preparatory stages